The sovereign credit default swap market – is there anything to be afraid of? A comparison of selected central and western european economies - Kliber, Agata (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
The paper concentrates on the impact of sovereign CDS (sCDS) on other financial markets within a country, and tests whether the impact changed after imposing the ban on trade of the non-covered sCDS in Europe (November 2012). The European sCDS of Poland, Hungary, and the Czech Republic (emerging markets) as well as Sweden and the United Kingdom (developed markets) are analysed over the period of 2008-2013. We investigate the influence between the sCDS and the foreign exchange market, sCDS and sovereign bonds, as well as sCDS and stock exchanges. The results vary depending on the liquidity and maturity of the analysed markets, indicating that the Central European markets used to be more prone to sunspots and volatility transmission than the Western ones. The study suggests that in most cases the impact of the CDS on other financial markets diminished after November 2012 and that the markets of speculative investment grade contributed most to the ban
Argumenta Oeconomica, 2019, Nr 2 (43), s. 137-167
Keywords: CDS; financial crisis; volatility; VAR; GARCH; Granger causality test; Hong test